2020
DOI: 10.1186/s40348-020-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

Random X chromosome inactivation in patients with Klinefelter syndrome

Abstract: Background: X chromosome inactivation (XCI) is an indispensable process in the development of human female embryos. Reportedly, XCI occurs when a blastocyst contains 10-12 embryonic progenitor cells. To date, it remains unclear whether XCI ratios are normally preserved in Klinefelter syndrome (KS) patients with 47,XXY karyotype. Methods: We examined XCI ratios in 18 KS patients through DNA methylation analysis for the polymorphic trinucleotide locus in the AR gene. The results of the KS patients were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Asprosin level is also elevated in obese children more significantly than in overweight children, with girls having higher levels than boys [ 35 ]. The current review of the literature in this area has been prepared by Janoschek et al [ 36 ]. On the basis of these findings, asprosin seems to be a factor favoring both the development of obesity and accompanying diseases such as DM2, while promoting the development of insulin resistance.…”
Section: Asprosin and Insulin Resistance Diabetes And Obesitymentioning
confidence: 99%
“…Asprosin level is also elevated in obese children more significantly than in overweight children, with girls having higher levels than boys [ 35 ]. The current review of the literature in this area has been prepared by Janoschek et al [ 36 ]. On the basis of these findings, asprosin seems to be a factor favoring both the development of obesity and accompanying diseases such as DM2, while promoting the development of insulin resistance.…”
Section: Asprosin and Insulin Resistance Diabetes And Obesitymentioning
confidence: 99%
“…Part of this dosage compensation system is the transcriptional silencing of one X in the somatic cells of females via the epigenetic process of XCI (2). In XXX human females, two Xs are inactivated (22), and in XXY males one X is silenced, leaving one active X (23,24). This is a reflection of the counting mechanism of XCI, which results in all but one X being silenced in mammals (25) and is entirely genotype dependent.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that SXI in KS patients occurs as a common genetic event ( Iitsuka et al, 2001 ). However, it has also been shown that 10–50% of KS patients present SXI ( Amos-Landgraf et al, 2006 ; Bojesen et al, 2011 ; Mehta et al, 2012 ; Kinjo et al, 2020 ). Our data show similar results to these studies.…”
Section: Discussionmentioning
confidence: 99%